The Frightened Land - Beningfield, Jennifer (Taylor & Francis, 2006)
An investigation into the spatial politics of separation and division in South Africa, principally during the apartheid years, and the effects of these physical and conceptual barriers on the land. In contrast to the weight of literature focusing on post-apartheid South Africa, the focus of this book includes the spatial, political and cultural landscape practices of the apartheid government and also refers to contemporary work done in Australia, England and the US. It probes the uncertainty and ambiguity of identities and cultures in post-apartheid society in order to gain a deep understanding of the history that individuals and society now confront. Drawing on a wealth of research materials including literature, maps, newspapers, monuments, architectural drawings, government legislation, tourist brochures, political writing and oral histories, this book is well illustrated throughout and is a unique commentary on the spatial politics of a time of enormous change.